COVID-19: Mental Health Prevention and Care for Healthcare Professionals - Rolling, Julie; Mengin, Amaury C.; Palacio, Cédric; Mastelli, Dominique; Fath, Morgane; Gras, Adrien; Von Hunolstein, Jean-Jacques; Schröder, Carmen M.; Vidailhet, Pierre (Frontiers in Psychiatry, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic exposed health professionals to high stress levels inducing significant psychological impact. Our region, Grand Est, was the most impacted French region during the first COVID-19 wave. In this context, we created CoviPsyHUS, local mental health prevention and care system dedicated explicitly to healthcare workers affected by the COVID-19 pandemic in one of this region's tertiary hospitals. We deployed CoviPsyHUS gradually in 1 month. To date, CoviPsyHUS comprises 60 mental health professionals dedicated to 4 complementary components: (i) a mental health support hotline (170 calls), (ii) relaxation rooms (used by 2,120 healthcare workers with 110 therapeutic workshops offered), (iii) mobile teams (1,200 contacts with healthcare staff), and (iv) a section dedicated to patients and their families. Among the critical points to integrate mental health care system during a crisis, we identified: (i) massive dissemination of mental health support information with multimodal communication, (ii) clear identification of the mental health support system, (iii) proactive mobile teams to identify healthcare professionals in difficulty, (iv) concrete measures to relieve the healthcare professionals under pressure (e.g., the relay in communication with families), (v) support for primary needs (body care (physiotherapy), advice and first-line therapy for sleep disorders), and (vi) psychoeducation and emotion management techniques. The different components of CoviPsyHUS are vital elements in meeting the needs of caregivers in situations of continuous stress. The organization of 4 targeted, modular, and rapidly deployable components makes CoviPsyHUS an innovative, reactive, and replicable mental health prevention and care system that could serve as a universal support model for other COVID-19 affected teams or other exceptional health crises in the future.